Characterization of starches from some selected white and yellow cassava roots for dry starch noodle production - Akinde, H.A.; Sanni, L.; Shittu, T.; Adegunwa, M.; Abass, A.; Awoyale, W. (Informa UK Limited, 2024)
Starch noodle, originally produced from mung bean starch, is now patronized in many parts of the world. Although cassava is one of the most abundant sources of starch in Nigeria, previous works determining its applicability for noodle production are scarce in literature. This study therefore determined the chemical properties of starches from selected white and yellow cassava for dry starch noodle production. Descriptive attributes and sensory acceptability of the starch noodle produced were also determined using commercial starch noodle as reference sample. Data obtained were subjected to analysis of variance using SPSS (version 21). Chemical properties of cassava starches varied significantly (p < .05). Using clustering and discriminant function analyses, two product clusters were identified with their distinct physical and sensory properties. This study showed that the most acceptable cassava starch noodles were obtained from TMS 01/1206 followed by TMS 01/1368, the least acceptable noodle was obtained from TME 419.